Crossover from incoherent to coherent thermal conduction in bulk titanium oxide natural superlattices. (1st February 2022) - Harada, Shunta; Kosaka, Naoki; Yagi, Takashi; Sugimoto, Shunya; Tagawa, Miho; Ujihara, Toru
Abstract: We have investigated thermal conduction in bulk titanium oxide natural superlattices with crystallographic shear (CS) structures, in which dense planar faults are introduced with different periodicities, prepared by reductive annealing of rutile TiO2 and crystal growth by the floating zone method. High-angle annular dark-field (HAADF) scanning transmission electron microscopy (STEM) revealed that (132)rutile and (121)rutile CS planes with interspacings of 2.7 and 1.0 nm were introduced in the mother rutile structure. Time-domain thermoreflectance (TDTR) revealed that the thermal conductivity decreased by the introduction of CS planes, but that the decrease is not monotonic with increasing density of CS planes. Calculation of the thermal conductivity and the mean free path for phonons revealed that a crossover from incoherent to coherent thermal conduction took place, and coherent interfaces with nanoscale periodicity were formed as thermodynamically stable phases in bulk titanium oxide natural superlattices. Graphical abstract: Image, graphical abstract